Ink for direct writing 3D printing of zinc ion batteries and preparation method thereof
By providing an ink containing PC/SiOC composite for direct writing of zinc ion batteries, the problem of slow transmission speed of the anode surface coating and growth of dendrites is solved, efficient zinc ion transmission and electrochemical performance is achieved, and the cycle life and rate performance of the battery is significantly improved.
Patent Information
- Application Number
- CN202210576480.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-25
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2042-05-25
AI Technical Summary
The deposition technology of existing zinc ion battery anode surface coating has the problems of slow zinc ion transfer speed, low conductivity and electrochemical activity, and cannot completely suppress dendrites' growth, resulting in low Coulomb efficiency, low capacity and limited cycle life.
An ink for direct writing 3D printing of zinc ion batteries is provided, comprising N-methylpyrrolidone, PC/SiOC composite material, polyvinylidene fluoride and conductive carbon black, which consists of porous carbon and interpenetrating silicone carbon networks, prepared by ball milling and vacuum filtration.
After printing and filming on the anode surface of the zinc ion battery, the ink improves the zinc ion transmission speed, enhances the conductivity and electrochemical activity, effectively inhibits dendrite growth, improves the capacity and rate performance of the zinc ion battery, and significantly extends the cycle life.
Smart Images

Figure CN114864861B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of zinc ion battery direct writing 3D printing, and in particular to an ink for zinc ion battery direct writing 3D printing and a preparation method thereof. Background Art
[0002] Rechargeable aqueous zinc-ion battery is an emerging and promising alternative energy storage technology. Because of its advantages such as high theoretical capacity (820mAh / g), low redox potential (-0.76V vs.SHE), abundant reserves, simple manufacturing and assembly, low cost, safety and environmental protection, it shows great potential in portable electronic applications and large-scale energy storage systems and has broad application prospects.
[0003] However, zinc-ion batteries face great challenges in practical applications. In particular, the dendrite growth of the metal zinc anode during the cyclic deposition / stripping process leads to low coulombic efficiency, low capacity, and limited cycle life of the zinc-ion battery. In order to solve the problem of anode dendrite growth and improve the cycle life and rate performance of zinc-ion batteries, the main method at present is to deposit a surface coating on the metal zinc anode. For example, Liu et al. developed a method of coating graphene oxide nanosheets on zinc metal anodes using a casting method to inhibit dendrite growth; the invention application CN114094035A discloses a method for preparing an aluminum-zinc alloy coating on the anode of a zinc-ion battery, which uses magnetron co-sputtering technology to prepare an aluminum-zinc alloy coating on the anode for anode protection; the invention application CN112952052A provides a zinc / carbon nanotube foam composite material as an anode material for a zinc-ion battery and discloses a method for preparing an anode using the composite material by high-temperature reaction and electrodeposition in the invention application CN112952053A.
[0004] However, the above-mentioned existing zinc ion battery anode surface coating deposition technology has the following disadvantages: the transmission speed of zinc ions on the anode surface is slow, and the electrical conductivity and electrochemical activity are not high, which limits the capacity and rate performance of the battery; the zinc ion diffusion area is limited and cannot completely inhibit the growth of dendrites, and there is still a risk of short circuit caused by dendrites, which limits the cycle life; the preparation process is complex and the cost is high.
[0005] Direct writing 3D printing is a low-cost, fast and high-precision additive manufacturing technology. Applying it to the deposition of zinc-ion battery anode surface coating is expected to solve the above problems. The key to applying direct writing 3D printing to zinc-ion battery manufacturing is to prepare ink with good printing performance and meet the functional requirements of fast zinc ion transmission speed on the anode surface, high conductivity and electrochemical activity, and expanding the zinc ion diffusion area to inhibit dendrite growth. However, there is currently no ink that meets the above requirements, which limits the application of direct writing 3D printing in zinc-ion battery manufacturing.
[0006] Therefore, the prior art still needs to be improved and developed. Summary of the invention
[0007] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide an ink for direct writing 3D printing of zinc ion batteries and a preparation method thereof, aiming to solve the shortcomings of the existing deposition technology of the surface coating of the anode of zinc ion batteries and the problem of lack of ink that meets the printing performance and functional requirements in the application of direct writing 3D printing in zinc ion battery manufacturing.
[0008] The technical solution of the present invention is as follows:
[0009] An ink for direct writing 3D printing of zinc ion batteries, comprising N-methylpyrrolidone and a PC / SiOC composite material dissolved in the N-methylpyrrolidone, polyvinylidene fluoride and conductive carbon black, wherein the PC / SiOC composite material consists of porous carbon and a silicon-oxygen-carbon network interpenetrating on the porous carbon.
[0010] The ink for direct writing 3D printing of zinc ion batteries, wherein the mass ratio of the PC / SiOC composite material, polyvinylidene fluoride and conductive carbon black is 8:1:1.
[0011] The method for preparing the ink for direct writing 3D printing of zinc ion batteries comprises the following steps:
[0012] Provide a PC / SiOC composite material, wherein the PC / SiOC composite material is composed of porous carbon and a silicon-oxygen-carbon network interpenetrating on the porous carbon;
[0013] Ball milling the PC / SiOC composite material, polyvinylidene fluoride and conductive carbon black to obtain a mixed powder;
[0014] dissolving the mixed powder in N-methylpyrrolidone to obtain an ink composition;
[0015] The lumps and large particles in the ink composition are removed by vacuum filtration, and the ink composition is allowed to stand for a predetermined time at room temperature to obtain the ink for direct writing 3D printing of zinc ion batteries.
[0016] The method for preparing the ink for direct writing 3D printing of zinc ion batteries, wherein, in the step of ball milling the PC / SiOC composite material, polyvinylidene fluoride and conductive carbon black to obtain a mixed powder, the mass ratio of the PC / SiOC composite material, polyvinylidene fluoride and conductive carbon black is 8:1:1.
[0017] The method for preparing the ink for direct writing 3D printing of zinc ion batteries, wherein the preparation of the PC / SiOC composite material comprises the steps of:
[0018] Preparation of isoreticular covalently functionalized zirconium-based MOF crystals, namely UiO-66-NH 2 Crystals;
[0019] The hexadecyl trimethyl ammonium bromide was dissolved in the PDSDA methanol solution in an ultrasonic bath to obtain a PDSDA / CTAB mixed solution; the UiO-66-NH2 crystals were dissolved in methanol under magnetic stirring to obtain UiO-66-NH 2 Solution;
[0020] The PDSDA / CTAB mixed solution was added to the UiO-66-NH 2 The solution was stirred at room temperature, and then after the polymerization reaction in MOFs was completed, argon degassing, sample collection, ethanol washing and vacuum drying were performed to obtain a UiO-66 / PDSDA composite.
[0021] The UiO-66 / PDSDA composite was pyrolyzed in an argon environment of a tube furnace to obtain a PC / SiOC composite material.
[0022] The method for preparing the ink for direct writing 3D printing of zinc ion batteries, wherein the UiO-66-NH 2 The preparation of crystals includes the steps of:
[0023] ZrCl 4 and H 2 NH 2 BDC was dissolved in HCON (CH 3 ) 2 , then add hydrochloric acid, hydrochloric acid and HCON (CH 3 ) 2 The volume ratio is 1:140 to obtain a mixed solution;
[0024] After stirring the mixed solution at room temperature for 30 minutes, the mixed solution was transferred to a polytetrafluoroethylene-lined autoclave and heated at 120 °C for 10 hours. After heating, the suspension was centrifuged to obtain a yellow powder product, which was then washed with anhydrous ethanol and then transferred to a Schlenk bottle and dried at ambient temperature to obtain UiO-66-NH 2 Crystal.
[0025] The method for preparing the ink for direct writing 3D printing of zinc ion batteries, wherein the step of pyrolyzing the UiO-66 / PDSDA composition in an argon environment of a tubular furnace to prepare a PC / SiOC composite material comprises:
[0026] The UiO-66 / PDSDA composite was placed in a tubular furnace and subjected to a three-stage pyrolysis process in an argon environment: in the first stage, the temperature was increased from 25°C to 400°C at a heating rate of 2°C / min, and then maintained at 400°C for two hours; in the second stage, the temperature was increased from 200°C to 800°C at a heating rate of 2°C / min, and maintained at 800°C for four hours; in the third stage, the temperature was reduced from 800°C to room temperature at a cooling rate of 2°C / min.
[0027] The method for preparing the ink for direct writing 3D printing of zinc ion batteries, wherein, in the PDSDA / CTAB mixed solution, the concentration of PDSDA is 0.01 g / mL, and the concentration of CTAB is 0.005 g / mL.
[0028] The method for preparing the ink for direct writing 3D printing of zinc ion batteries, wherein the UiO-66-NH 2 The concentration of the solution is 0.01455 g / mL.
[0029] The method for preparing the ink for direct writing 3D printing of zinc ion batteries, wherein the PDSDA / CTAB mixed solution is added to the UiO-66-NH 2 In the solution step, the PDSDA / CTAB mixed solution was mixed with UiO-66-NH 2 The mass ratio of the solution is 1:3.
[0030] Beneficial effects: The ink provided by the present invention has good viscosity characteristics, shear thinning characteristics, and shape retention characteristics. The anode surface coating obtained by using the ink has high dimensional accuracy, smooth surface, and good printability. After the ink provided by the present invention is printed into a film on the anode surface of a zinc ion battery, the transmission speed of zinc ions on the anode surface can be improved, and the film also has the characteristics of high electrical conductivity and high electrochemical activity, which improves the capacity and rate performance of the zinc ion battery, and the fast zinc ion transmission speed and large diffusion area can effectively inhibit dendrite growth and greatly improve the functional requirements of cycle life. The zinc ion battery with a complete anode structure obtained by direct writing 3D printing using the ink prepared by the present invention still has a high capacity of 67mAh / g after 2453 cycles at a current density of 0.5A / g, has good cycle life and rate performance, is of great significance to the direct writing 3D printing development of zinc ion batteries with high life and high rate characteristics, and has high practicality. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 The present invention is a flow chart of a method for preparing ink for direct writing 3D printing of zinc ion batteries.
[0032] Figure 2 Schematic diagram of the chemical reaction principle of the PC / SiOC composite material in the present invention.
[0033] Figure 3 a is a SEM image of the PC / SiOC composite material obtained in Example 1 of the present invention; b is a SEM image of the UiO-66-NH obtained in Example 1 of the present invention 2 a is the SEM image of the crystal; c is the SEM image of the PC alone in Example 1 of the present invention.
[0034] Figure 4 a is a TEM image of the PC / SiOC composite material obtained in Example 1 of the present invention; b is a high-resolution TEM image of the PC / SiOC composite material obtained in Example 1 of the present invention.
[0035] Figure 5 Schematic diagram of the viscosity-shear rate curve of the ink obtained in Example 1 of the present invention.
[0036] Figure 6 Schematic diagram of the storage modulus (G') and loss modulus (G")-angular frequency curves obtained in Example 1 of the present invention.
[0037] Figure 7 Figure a is a schematic diagram of the SEM characterization picture of the surface coating of the zinc ion battery anode obtained in Example 2 of the present invention in the horizontal direction; Figure b is a schematic diagram of the SEM characterization picture of the surface coating of the zinc ion battery anode obtained in Example 2 of the present invention in the height direction.
[0038] Figure 8 It is a schematic diagram of the cycle life and rate characteristics of the complete batteries of Example 3, Comparative Example 1 and Comparative Example 2 of the present invention at a current density of 0.5 A / g. DETAILED DESCRIPTION
[0039] The present invention provides an ink for direct writing 3D printing of zinc ion batteries and a preparation method thereof. In order to make the purpose, technical scheme and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0040] The present invention provides an ink for direct writing 3D printing of zinc ion batteries, comprising N-methylpyrrolidone (NMP) and a PC / SiOC composite material, polyvinylidene fluoride (PVDF) and conductive carbon black dissolved in the N-methylpyrrolidone, wherein the PC / SiOC composite material consists of porous carbon and a silicon-oxygen-carbon network interpenetrating on the porous carbon.
[0041] Specifically, the PC / SiOC composite material in the present invention has an electrode-optimized three-dimensional grid structure, which can quickly reverse, carry and guide divalent zinc ions, while limiting the direct contact between the organic electrolyte and the anode, and the PC / SiOC composite material has strong molecular coordination, which can provide a larger rapid diffusion area for zinc ions to effectively control dendrite growth. Based on this, the ink provided by the present invention can improve the transmission speed of zinc ions on the anode surface after being printed into a film on the anode surface of the zinc ion battery, and the film also has the characteristics of high conductivity and high electrochemical activity, which improves the capacity and rate performance of the zinc ion battery, and the fast zinc ion transmission speed and large diffusion area can effectively inhibit dendrite growth and greatly improve the functional requirements of cycle life; the ink prepared by the present invention is used for direct writing 3D printing to obtain a complete zinc ion battery with an anode, and at a current density of 0.5A / g, it still has a high capacity of 67mAh / g after 2453 cycles, has a good cycle life and rate performance, and has great significance for the direct writing 3D printing development of zinc ion batteries with high life and high rate characteristics, and has high practicality.
[0042] In some embodiments, the present invention also provides a method for preparing ink for direct writing 3D printing of zinc ion batteries, such as Figure 1 As shown, it includes the steps of:
[0043] S10, providing a PC / SiOC composite material, wherein the PC / SiOC composite material consists of porous carbon and a silicon-oxygen-carbon network interpenetrating on the porous carbon;
[0044] S20, ball-milling the PC / SiOC composite material, polyvinylidene fluoride and conductive carbon black to obtain a mixed powder;
[0045] S30, dissolving the mixed powder in N-methylpyrrolidone to obtain an ink composition;
[0046] S40, removing lumps and large particles in the ink composition by vacuum filtration, and leaving it to stand at room temperature for a predetermined time to obtain the ink for direct writing 3D printing of zinc ion batteries.
[0047] In the present embodiment, the mass ratio of the PC / SiOC composite material, polyvinylidene fluoride and conductive carbon black is 8:1:1. The ink prepared in the present embodiment has good viscosity characteristics, shear thinning characteristics, and shape retention characteristics. The anode surface coating obtained by using the ink has high dimensional accuracy, smooth surface, and good printability. After the ink provided in the present embodiment is printed into a film on the anode surface of the zinc ion battery, it can not only improve the transmission speed of zinc ions on the anode surface, but also the film has the characteristics of high electrical conductivity and high electrochemical activity, which improves the capacity and rate performance of the zinc ion battery, and the fast zinc ion transmission speed and large diffusion area can effectively inhibit dendrite growth and greatly improve the functional requirements of cycle life.
[0048] In some embodiments, the preparation of the PC / SiOC composite material comprises the steps of: 4 and H 2 NH 2 BDC was dissolved in HCON (CH 3 ) 2 , then add hydrochloric acid, hydrochloric acid and HCON (CH 3 ) 2 The volume ratio of the mixed solution was 1:140 to obtain a mixed solution; after stirring the mixed solution at room temperature for 30 minutes, the mixed solution was transferred to a polytetrafluoroethylene-lined autoclave and heated at 120°C for 10 hours. After heating, the suspension was centrifuged to obtain a yellow powder product, which was then washed with anhydrous ethanol and then transferred to a Schlenk bottle and dried at ambient temperature to obtain UiO-66-NH 2 crystals; dissolving hexadecyltrimethylammonium bromide (CTAB) in a PDSDA (poly[(silyl)diacetylene]) methanol solution in an ultrasonic bath to obtain a PDSDA / CTAB mixed solution; dissolving the UiO-66-NH2 crystals in methanol under magnetic stirring to obtain UiO-66-NH 2 solution; adding the PDSDA / CTAB mixed solution to the UiO-66-NH 2The solution is stirred at room temperature, and then after the polymerization reaction in MOFs is completed, argon degassing, sample collection, ethanol washing and vacuum drying are carried out to obtain a UiO-66 / PDSDA composite; the UiO-66 / PDSDA composite is placed in a tubular furnace and subjected to a three-stage pyrolysis process in an argon environment: in the first stage, the temperature is increased from 25°C to 400°C at a heating rate of 2°C / min, and then the temperature is maintained at 400°C for two hours; in the second stage, the temperature is increased from 200°C to 800°C at a heating rate of 2°C / min, and maintained at 800°C for four hours; in the third stage, the temperature is reduced from 800°C to room temperature at a cooling rate of 2°C / min to obtain a PC / SiOC composite material.
[0049] Specifically, if Figure 2 As shown, in this embodiment, UiO-66-NH 2 crystals, and then the PDSDA / CTAB mixed solution was mixed with the UiO-66-NH 2 The solution was stirred and mixed, during which the linear PDSDA could react with UiO-66-NH 2 -NH on the crystal 2 reaction, thereby binding PDSDA to UiO-66-NH 2 On the crystal, a UiO-66 / PDSDA composite is generated; finally, the UiO-66 / PDSDA composite is subjected to a pyrolysis treatment. In the first stage, a polymerization reaction can occur between multiple PDSDAs in the UiO-66 / PDSDA composite, and / or a polymerization reaction can occur between the PDSDAs between adjacent UiO-66 / PDSDA composites, so that the PDSDA on the UiO-66 forms a cross-linked network; in the second stage, high-temperature heating causes the Si-C bonds in the cross-linked network-like PDSDA to break, thereby forming a SiOC network, and the SiOC network is interpenetrated on the porous carbon matrix to form the PC / SiOC composite material, the matrix of the PC / SiOC composite material is the MOF framework, and the composite network SiOC structure expands the specific surface area, conductivity, electrochemical activity, etc. of the material, so that the material has a huge advantage in the application of zinc ion battery anode.
[0050] In this embodiment, the CTAB, as a surfactant, helps to destroy the polymerization attraction between the PDSDA polymer chains themselves, so that the PDSDA polymer chains can be better composited to the MOF framework to form a UiO-66 / PDSDA composite.
[0051] In this embodiment, in the PDSDA / CTAB mixed solution, the concentration of PDSDA is 0.01 g / mL, and the concentration of CTAB is 0.005 g / mL; the UiO-66-NH 2 The concentration of the solution was 0.01455 g / mL; the PDSDA / CTAB mixed solution and UiO-66-NH 2 The mass ratio of the solution is 1:3.
[0052] The present invention is further explained below by specific embodiments:
[0053] Example 1
[0054] A method for preparing ink is provided, comprising the following steps:
[0055] S1. Prepare a composite material for an anode, the specific operation is as follows:
[0056] S101, 1.50 g, 6.4 mmol ZrCl 4 and 1.56 g, 6.4 mmol of H 2 NH 2 BDC was dissolved in 280 mL of HCON (CH 3 ) 2 Then add 2mL of 36wt% hydrochloric acid to make the hydrochloric acid and HCON (CH 3 ) 2 The volume ratio of ZrCl is 1:140. 4 and H 2 NH 2 The concentration of BDC was 0.023 mol / L, ranging from 0.02 mol / L to 0.025 mol / L. The mixed solution was then stirred at room temperature for thirty minutes, and then the mixture was transferred to a 500 mL polytetrafluoroethylene-lined autoclave and heated at 120 °C for ten hours. After heating, the suspension was centrifuged to obtain a yellow powder product, which was then washed with anhydrous ethanol and then transferred to a Schlenk flask and dried at ambient temperature to obtain UiO-66-NH 2 Crystals;
[0057] S102, dissolving 0.5 g of CTAB in a 100 mL PDSDA-methanol solution with a concentration of 0.01 g / mL in an ultrasonic bath to perform polymerization reaction to obtain a PDSDA / CTAB mixed solution, so that the concentration of CTAB in the mixed solution is 0.005 g / mL; and mixing 1.455 g of UiO-66-NH obtained in step S101 under magnetic stirring. 2 The crystals were dissolved in 100 mL of methanol in a Schlenk bottle to obtain a concentration of 0.01455 g / L UiO-66-NH 2Solution;
[0058] S103, the PDSDA / CTAB mixed solution obtained in step S102 was quickly immersed in an argon environment at a mass ratio of 1:3 into a container containing UiO-66-NH 2 The solution was first stirred vigorously at room temperature for thirty minutes, and then the polymerization reaction within the MOFs was completed for three hours. The Schlenk flask was then degassed with argon, and then the sample was collected using a rotary evaporator, washed with ethanol, and finally dried in a vacuum oven set at 80°C overnight to obtain the UiO-66 / PDSDA synthesis;
[0059] S104. The UiO-66 / PDSDA composition obtained in step S103 is placed in a tubular furnace and subjected to a three-stage pyrolysis process in an argon environment: in the first stage, the temperature is increased from 25°C to 400°C at a heating rate of 2°C / min, and then maintained at 400°C for two hours; in the second stage, the temperature is increased from 200°C to 800°C at a heating rate of 2°C / min, and maintained at 800°C for four hours; in the third stage, the temperature is reduced from 800°C to room temperature at a cooling rate of 2°C / min.
[0060] S2. Prepare anode composite material coating ink suitable for 3D printing, the specific operation is as follows:
[0061] S201, firstly, uniformly mixing the PC / SiOC composite material obtained in step S1 with PVDF and conductive carbon black in a mass ratio of 8:1:1 by planetary ball milling, and then dissolving the mixed powder in an NMP solution to obtain a homogeneous ink composition;
[0062] S202, removing lumps and large particles from the ink composition in step S201 by vacuum filtration to prevent nozzle clogging, and then standing at room temperature for twelve hours to obtain a stable anode composite coating ink suitable for 3D printing.
[0063] Example 2
[0064] The ink obtained in Example 1 was used to prepare the zinc ion battery anode:
[0065] The ink obtained in Example 1 was printed on one side of zinc and stainless steel foil by direct writing 3D printing technology. The specific operation was as follows: the ink obtained in step Example 1 was gently stirred, and then loaded into a 10mL syringe needle connected to a lockable stainless steel blunt nozzle with an inner diameter of 200μm, and then the computer-aided design software SolidWorks Corporation was used to control the ink flow rate and printing speed in the low-temperature direct writing 3D printer to be 18mm / s, and the ink in the syringe needle was extruded through the lockable stainless steel blunt nozzle and printed on one side of the zinc and stainless steel foil to obtain an anode in an uncured state of the composite material coating; then, the 3D printed anode was placed in a vacuum oven for drying to obtain a cured anode product. The specific operation was as follows: the anode in the uncured state of the obtained composite material coating was placed in a vacuum oven, and the temperature of the vacuum oven was set to 80°C for twelve hours to obtain a cured anode product.
[0066] Example 3
[0067] The anode obtained in Example 2 was used to prepare a zinc ion battery:
[0068] The anode prepared in Example 2 was used as the negative electrode of the battery, a 2400 porous polypropylene separator with a thickness of 25 μm produced by Celgard Company of the United States was used as the diaphragm, 3M ZnSO4 deionized water was used as the electrolyte, and a V2O5 flat plate coated with V2O5 / C was used as the positive electrode to build a complete battery (denoted as V2O5 / C|3DP-PC / SiOC@Zn).
[0069] First, the structural properties of the PC / SiOC composite material prepared by the present invention were verified. The PC / SiOC composite material prepared in Example 1 was characterized in terms of material morphology and structure using a scanning electron microscope (SEM) of model JEOL-6700 and a transmission electron microscope (TEM) of model JEOL-2100F. During the SEM analysis, an energy dispersive X-ray spectrometer was used to perform dispersion spectrum analysis (EDS) to obtain detailed information on the element distribution and phase structure of the composite material. The results are as follows: Figure 3 (a) is a SEM image of the PC / SiOC composite material, showing that the spherical particle size of the carbon shell containing ZrO2 in the composite material is about 100nm. Figure 3 (b) is a SEM image of the UiO-66-NH2 crystal obtained in step S1 of Example 1, Figure 3 (c) is the SEM image of PC alone, compared with the attached Figure 3 (a) and (c) Figure 3 (b) and Figure 3 (c) shows that the morphology of the PC / SiOC composite material after polymerization and pyrolysis is consistent with the initial UiO-66-NH2 crystal morphology; Figure 4(a) is a TEM image of the PC / SiOC composite, indicating that the PC / SiOC composite retains the structure of the parent UiO-66-NH2 crystal, has retained porosity and is coordinated with the SiOC network interpenetrating with the PC surface, creating a large number of active sites for ion storage; Figure 4 (b) is a high-resolution TEM image of the PC / SiOC composite material, indicating that the PC / SiOC composite material has obvious screw dislocations, particle clusters and grain boundaries, which are derived from the SiOC coordination between ZrO2 crystals in different adjacent shells, and the interpenetrating SiOC network in PC can be used as a conductive network to create more active sites and improve the charge transfer performance; the structural performance test of the PC / SiOC composite material shows that: the PC / SiOC composite material in Example 1 obtained by the present invention has an electrode-optimized three-dimensional grid structure, which can quickly reverse, carry and guide divalent zinc ions, while limiting the direct contact between the organic electrolyte and the anode, and has strong molecular coordination, which can provide a larger rapid diffusion area for zinc ions to effectively control dendrite growth.
[0070] Secondly, the printability of the ink prepared by the method proposed in the present invention was verified. The ink prepared in Example 1 was subjected to viscosity-shear rate experiments and oscillation experiments using a rheometer model MCR 92 of Anton Paar GmbH, Austria to analyze the printability of the ink. Then, the ink deposition layer on the anode obtained in Example 2 was characterized by a scanning electron microscope (SEM) model JEOL-6700. The results are as follows: Figure 5 The viscosity-shear rate curve of the ink obtained by the viscosity-shear rate experiment for the ink obtained in Example 1 shows that the viscosity of the ink is at a low shear rate (0.1s -1 ) is 2971Pa·s, and has a very good shear thinning property, so the ink maintains good stability and high viscosity at low shear rates, and maintains shear thinning properties at higher shear rates to allow the ink to be squeezed through the nozzle, with good printing performance; attached Figure 6 : The storage modulus (G') and loss modulus (G")-angular frequency diagram obtained by oscillation experiment for the ink obtained in Example 1. It can be seen that G' is always higher than G", which indicates that the ink has good shape retention properties after printing; Figure 7 (a) and Figure 7(b) are SEM images of the surface coating on the anode obtained in Example 2 in the horizontal and height directions, respectively, from which it can be seen that the anode surface coating obtained using the ink has high dimensional accuracy and a smooth surface; in summary, it is proved that the ink prepared by the method proposed in the present invention has good viscosity characteristics, shear thinning characteristics, and shape retention characteristics, and the anode surface coating obtained using the ink has high dimensional accuracy, a smooth surface, and good printability.
[0071] Then, in order to verify the cycle life and rate performance of the zinc ion battery constructed by the anode obtained by the ink prepared by the method proposed in the present invention, a comparative example was set to compare the electrical performance of the complete battery in Example 3, and the comparative example was set as follows:
[0072] Comparative Example 1
[0073] In Comparative Example 1, the ink preparation process is the same as that of Example 1, but in the process of preparing the anode, the ink is horizontally coated on one side of the zinc and stainless steel foils instead of printing the ink on one side of the zinc and stainless steel foils using direct writing 3D printing technology. The obtained anode is used as the negative electrode of the battery, a 2400 porous polypropylene separator with a thickness of 25 μm produced by Celgard Company of the United States is used as the diaphragm, 3M ZnSO4 deionized water is used as the electrolyte, and V 2 O 5 Flat Coating V 2 O 5 / C plate is used as the positive electrode to build a complete battery.
[0074] Comparative Example 2
[0075] In Comparative Example 2, 0.1 mm thick zinc and stainless steel foil without any coating were directly used as anodes as negative electrodes of the battery, 2400 porous polypropylene separators with a thickness of 25 μm produced by Celgard Company of the United States were used as separators, 3M ZnSO4 deionized water was used as electrolyte, and V 2 O 5 Flat Coating V 2 O 5 / C flat plate is used as the positive electrode to build a complete battery.
[0076] The complete batteries in Example 3 and Comparative Examples 1-2 were subjected to electrical performance tests and comparisons, and rate capacity and cycle performance tests were performed using a battery tester model LANHE-CT2001A produced by Wuhan Shenglan Electronic Technology Co., Ltd. The test and comparison results are as follows: Figure 8The zinc ion battery obtained by direct writing 3D printing using the ink prepared by the present invention still has a high capacity of 67 mAh / g after 2453 cycles at a current density of 0.5 A / g; in contrast, the number of complete battery cycles in comparative example 1 is 1880 times, and the capacity is 58 mAh / g; the number of complete battery cycles in comparative example 2 is 128 times, and the capacity is 13 mAh / g; therefore, the comparison between Example 3 and comparative examples 1 and 2 proves that the ink proposed by the present invention has the functional requirements of improving the cycle life and rate performance of zinc ion batteries.
[0077] In summary, the direct writing 3D printing ink obtained by the present invention has good printing performance, and has the characteristics of fast zinc ion transmission speed on the anode surface, high electrical conductivity and electrochemical activity, high battery capacity and rate performance, large zinc ion diffusion area, which can effectively inhibit dendrite growth and greatly improve the functional requirements of cycle life, and the preparation process is simple and low in cost, with strong practicality, which is of great significance to the direct writing 3D printing development of zinc ion batteries with long life and high rate characteristics, and has high practicality.
[0078] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.
Claims
1. An ink for direct writing 3D printing of zinc ion batteries, characterized in that: It includes N-methylpyrrolidone and a PC / SiOC composite material dissolved in the N-methylpyrrolidone, polyvinylidene fluoride and conductive carbon black, wherein the PC / SiOC composite material consists of porous carbon and a silicon-oxygen-carbon network interpenetrating on the porous carbon; The PC / SiOC composite material is prepared by pyrolyzing a UiO-66 / PDSDA composite obtained by reacting a network covalently functionalized zirconium-based MOF crystal, i.e., a UiO-66-NH2 crystal, with PDSDA; The preparation of the PC / SiOC composite material comprises the following steps: Preparation of isoreticular covalently functionalized zirconium-based MOF crystals, namely UiO-66-NH2 crystals; Dissolving hexadecyltrimethylammonium bromide in a polydimethylsilane diacetylene (PDSDA) methanol solution in an ultrasonic bath to obtain a PDSDA / CTAB mixed solution; dissolving the UiO-66-NH2 crystals in methanol under magnetic stirring to obtain a UiO-66-NH2 solution; The PDSDA / CTAB mixed solution is added to the UiO-66-NH2 solution in an argon environment, stirred at room temperature, and then after the polymerization reaction in MOFs is completed, argon degassing, sample collection, ethanol washing and vacuum drying are performed to obtain a UiO-66 / PDSDA synthetic material; The UiO-66 / PDSDA composite is subjected to pyrolysis treatment in an argon environment of a tube furnace to obtain a PC / SiOC composite material; The step of pyrolyzing the UiO-66 / PDSDA composition to obtain a PC / SiOC composite material comprises: The UiO-66 / PDSDA composite was placed in a tube furnace and subjected to a three-stage pyrolysis process in an argon environment: in the first stage, the temperature was increased from 25°C to 400°C at a heating rate of 2°C / min, and then the temperature was maintained at 400°C for two hours; in the second stage, the temperature was increased from 200°C to 800°C at a heating rate of 2°C / min, and maintained at 800°C for four hours; in the third stage, the temperature was reduced from 800°C to room temperature at a cooling rate of 2°C / min; The preparation of the UiO-66-NH2 crystal comprises the following steps: Dissolve zirconium tetrachloride ZrCl4 and 2-aminoterephthalic acid H2N-H2BDC in N,N-dimethylformamide HCON(CH3)2 at the same concentration of 0.02mol / L-0.025mol / L, then add hydrochloric acid, the volume ratio of hydrochloric acid to HCON(CH3)2 is 1:140, to obtain a mixed solution; After stirring the mixed solution at room temperature for 30 minutes, the mixed solution was transferred to a polytetrafluoroethylene-lined autoclave and heated at 120°C for 10 hours. After heating, the suspension was centrifuged to obtain a yellow powder product, which was then washed with anhydrous ethanol and then transferred to a Schlenk flask and dried at ambient temperature to obtain UiO-66-NH2 crystals; The UiO-66 is a zirconium-based metal organic framework material, the core of which is composed of zirconium oxygen clusters and terephthalic acid ligands, wherein the zirconium oxygen cluster is a hexanuclear zirconium oxygen cluster Zr6O4(OH)4, and each cluster is connected by 12 terephthalic acid ligands to form a three-dimensional porous network with high stability and porous properties. Terephthalic acid can regulate material properties through functionalization.
2. The ink for direct writing 3D printing of zinc ion batteries according to claim 1, characterized in that: The mass ratio of the PC / SiOC composite material, polyvinylidene fluoride and conductive carbon black is 8:1:
1.
3. The method for preparing ink for direct writing 3D printing of zinc ion batteries according to claim 1, characterized in that, Includes steps: Provide a PC / SiOC composite material, wherein the PC / SiOC composite material is composed of porous carbon and a silicon-oxygen-carbon network interpenetrating on the porous carbon; Ball milling the PC / SiOC composite material, polyvinylidene fluoride and conductive carbon black to obtain a mixed powder; dissolving the mixed powder in N-methylpyrrolidone to obtain an ink composition; The lumps and large particles in the ink composition are removed by vacuum filtration, and the ink composition is allowed to stand for a predetermined time at room temperature to obtain the ink for direct writing 3D printing of zinc ion batteries.
4. The method for preparing ink for direct writing 3D printing of zinc ion batteries according to claim 3, characterized in that, In the step of ball-milling the PC / SiOC composite material, polyvinylidene fluoride and conductive carbon black to obtain a mixed powder, the mass ratio of the PC / SiOC composite material, polyvinylidene fluoride and conductive carbon black is 8:1:
1.
5. The method for preparing ink for direct writing 3D printing of zinc ion batteries according to claim 3, characterized in that, In the PDSDA / CTAB mixed solution, the concentration of PDSDA is 0.01 g / mL, and the concentration of CTAB is 0.005 g / mL.
6. The method for preparing ink for direct writing 3D printing of zinc ion batteries according to claim 3, characterized in that: The concentration of the UiO-66-NH2 solution is 0.01455 g / mL.
7. The method for preparing ink for direct writing 3D printing of zinc ion batteries according to claim 3, characterized in that: In the step of adding the PDSDA / CTAB mixed solution to the UiO-66-NH2 solution in an argon environment, the mass ratio of the PDSDA / CTAB mixed solution to the UiO-66-NH2 solution is 1:3.
Citation Information
Patent Citations
3D printing zinc ion battery positive electrode and preparation method thereof
CN113054152A
Silicon-oxygen-carbon composite material as well as preparation method and application thereof
CN114175309A